2014
DOI: 10.1371/journal.pone.0100512
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Markers Reveal High Genetic Diversity but Low Genetic Differentiation in the Black Fly Simulium tani Takaoka & Davies along an Elevational Gradient in Malaysia

Abstract: The population genetic structure of Simulium tani was inferred from mitochondria-encoded sequences of cytochrome c oxidase subunits I (COI) and II (COII) along an elevational gradient in Cameron Highlands, Malaysia. A statistical parsimony network of 71 individuals revealed 71 haplotypes in the COI gene and 43 haplotypes in the COII gene; the concatenated sequences of the COI and COII genes revealed 71 haplotypes. High levels of genetic diversity but low levels of genetic differentiation were observed among po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Of the five genetic markers in our study, the COI gene is more variable and informative in resolving interspecific relationships among the members of the S. ceylonicum and S. asakoae species groups. The COI gene has been the genetic marker of choice for blackflies in studies of DNA barcoding (Rivera & Currie, ; Pramual et al ., ; Pramual & Adler, ), phylogenetics (Conflitti et al ., ; Phayuhasena et al ., ; Pramual et al ., ), and phylogeography (Pramual et al ., ; Finn & Adler, ; Low et al ., ). The value of this marker in revealing the cryptic biodiversity of blackflies has been documented (Pramual et al ., ; Pramual & Nanork, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the five genetic markers in our study, the COI gene is more variable and informative in resolving interspecific relationships among the members of the S. ceylonicum and S. asakoae species groups. The COI gene has been the genetic marker of choice for blackflies in studies of DNA barcoding (Rivera & Currie, ; Pramual et al ., ; Pramual & Adler, ), phylogenetics (Conflitti et al ., ; Phayuhasena et al ., ; Pramual et al ., ), and phylogeography (Pramual et al ., ; Finn & Adler, ; Low et al ., ). The value of this marker in revealing the cryptic biodiversity of blackflies has been documented (Pramual et al ., ; Pramual & Nanork, ).…”
Section: Discussionmentioning
confidence: 99%
“…() for 16S rRNA, and Low et al . () for 18S rRNA and 28S rRNA. Primers used for amplification of these five genes are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…The greater genetic diversity of S. (S.) gravelyi was observed at high elevational site (1590 m) using RAPD (Anbalagan et al, 2012). Further, dissolved oxygen in stream had a strong relationship with nucleotide diversity of S. (S.) tani in Malaysia (Low et al, 2014). The distributions of black flies, from cytotypes and molecular forms to full species, typically are related with stream profiles of pH, stream size and water temperature (Grunewald, 1981;Maraun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity studies in black flies have been conducted on Simulium gravelyi by Random Amplified Polymorphic DNA (RAPD) (Anbalagan et al, 2012), Psilopelmia by internal transcribed spacer 1 of the nuclear ribosomal RNA gene (Tang et al, 1998), Cnephia by DNA barcode gene (Conflitti et al, 2013) and Simulium tani by DNA barcoding genes (COI and COII) (Low et al, 2014). Less attention has received on DNA barcode based RFLP analysis in black fly.…”
Section: Introductionmentioning
confidence: 99%
“…The aquatic dissolved oxygen was reported as a selective force limiting gene flow among populations and therefore played a key role in determining the genetic structure of populations (Robert, Merritt, Chapman, David, & Martinez, ). Genetic study in Simulium tani also showed that nucleotide diversity was strongly correlated to the levels of dissolved oxygen in the streams (Low, Adler, & Takaoka, ). The cold water fish Cottus poecilopus was also reported to be abundant in streams with high oxygen saturation and high abundance of macroinvertebrates (Baran et al, ).…”
Section: Discussionmentioning
confidence: 99%